Comparison of seven housekeeping genes expression in microalgae (Chlorella vulgaris) grown under nitrogen limited condition - Jessreen Tega; Nor ‘Awatif Che Soh; Siti Nurul Amira Noor Azman; Cha, Thye San; Malinna Jusoh (Penerbit Universiti Kebangsaan Malaysia, 2020)
The study of the lipid synthesis pathway and the gene expression analysis of microalgae is crucial to understand more about the genes that play roles in lipid synthesis. The use of real-time polymerase chain reaction (PCR) in gene expression analysis is the best choice and it necessitates housekeeping genes (HKGs) as internal standard controls. It is essential to establish stable reference genes for the proper normalization. This study aimed at evaluating the stability of seven HKGs of microalgae, Chlorella vulgaris which were actin, alpha-tubulin, beta-tubulin, elongation factor, cyclophilin, 18S rRNA, and GAPDH that were grown under nitrogen-limited condition. C. vulgaris were grown in complete F/2 media with NaNO3 concentration of 8.82 x 10-4 M for control and 2.2 x10-4 M (25%) of NaNO3 for the nitrogen-limited condition. The cultures were grown for 28 days and RNA extraction was done at intervals of 7 days. Cycle threshold (Ct) values of control and treatment were generated from real-time PCR to evaluate the stability of HKGs. Results showed a significant stable expression of cyclophilin (28.04 ± 1.10 for control and 29.17 ± 1.06 for treatment) and GAPDH (37.23 ± 0.30 for control and 36.44 ± 0.53 for treatment). Meanwhile, other HKGs showed significant unstable expression. Thus, cyclophilin and GAPDH can be used as a reference gene of C. vulgaris for lipid production.